Moral categories in the financial crisis - Marion Fourcade; Philippe Steiner; Wolfgang Streeck; Cornelia Woll (Max Planck Sciences Po Center on Coping with Instability in Market Societies (MaxPo), 2013)
Karl Marx observed long ago that all economic struggles invite moral struggles, or masquerade as such. The reverse may be true as well: deep moral-political conflicts may be waged through the manipulation of economic resources. Using the recent financial and Eurozone crises as empirical backgrounds, the four papers gathered here propose four different perspectives on the play of moral judgments in the economy, and call for broader and more systematic scholarly engagement with this issue. Focusing on executive compensation, bank bailouts, and the sovereign debt crisis, the symposium builds on a roundtable discussion held at the opening of the Max Planck Sciences Po Center on Coping with Instability in Market Societies (MaxPo) in Paris on November 29, 2012.
Keywords: 330